2010
DOI: 10.1007/s10021-010-9338-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant Species Composition Can Be Used as a Proxy to Predict Methane Emissions in Peatland Ecosystems After Land-Use Changes

Abstract: Land-use change in peatlands affects important drivers of CH 4 emission such as groundwater level and nutrient availability. Due to the high spatial and temporal variability of such environmental drivers, it is hard to make good predictions of CH 4 emissions in the context of land-use changes. Here, we used plant species composition as a stable integrator of environmental drivers of CH 4 emissions. We used weighted averaging regression and calibration to make a direct link between plant species composition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 31 publications
5
48
0
Order By: Relevance
“…Veenendaal et al (2007), for example, assumed that intensively managed grassland on peat emits very little methane (0.005 mg CH 4 m −2 h −1 ). Schrier-Uijl et al (2010a) as well as Dias et al (2010) reported higher fluxes (~1 and 0.03 mg CH 4 m −2 h −1 ), but earlier work of suggest that intensively used well-drained grassland is a net sink for CH 4 (−0.003 mg CH 4 m −2 h −1 ). At the same time, these drained peatlands emit substantial quantities of CO 2 and N 2 O, and all should be included when estimating a full greenhouse gas balance (Hendriks et al 2007;Kechavarzi et al 2007;Veenendaal et al 2007).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Veenendaal et al (2007), for example, assumed that intensively managed grassland on peat emits very little methane (0.005 mg CH 4 m −2 h −1 ). Schrier-Uijl et al (2010a) as well as Dias et al (2010) reported higher fluxes (~1 and 0.03 mg CH 4 m −2 h −1 ), but earlier work of suggest that intensively used well-drained grassland is a net sink for CH 4 (−0.003 mg CH 4 m −2 h −1 ). At the same time, these drained peatlands emit substantial quantities of CO 2 and N 2 O, and all should be included when estimating a full greenhouse gas balance (Hendriks et al 2007;Kechavarzi et al 2007;Veenendaal et al 2007).…”
Section: Discussionmentioning
confidence: 91%
“…Since water may cover anywhere between 6 and 43% in these peatlands (Vermaat and Hellmann 2010), our findings imply that landscapescale assessments of methane fluxes require separate estimates of terrestrial and aquatic fluxes, where the latter need to take into account productivity and groundwater table (Kechavarzi et al 2007) of the adjacent land. We did a tentative landscape-scale estimate using our own aquatic CH 4 fluxes at annual mean temperature, terrestrial estimates from Dias et al (2010), and a methane emission estimate for dairy cattle from Veenendaal et al (2007). We conclude that agricultural landscapes would emit more methane than natural wetlands only if the percentage of open water was above 65%.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Metaanalysis of available annual CO 2 flux data denied a distinction between bog and fen sites; fluxes rather are determined by water level, allowing the use of 'bog' measurements to specify CO 2 fluxes from 'fen' sites and vice versa. A strong relationship between dominant plant species and methane emissions has been described for two Dutch peatlands (Dias et al, 2010). The presence or absence of aerenchymous shunt species provides a first simple division of vegetation and flux data, which enables assigning flux values to vegetation types not covered by direct flux measurements.…”
Section: Ascribing Emission Factors To Vegetation Typesmentioning
confidence: 99%